2016
DOI: 10.1371/journal.ppat.1005840
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-Based Therapy Protects Against Influenza by Promoting Lung Repair and Recovery in Females

Abstract: Over 100 million women use progesterone therapies worldwide. Despite having immunomodulatory and repair properties, their effects on the outcome of viral diseases outside of the reproductive tract have not been evaluated. Administration of exogenous progesterone (at concentrations that mimic the luteal phase) to progesterone-depleted adult female mice conferred protection from both lethal and sublethal influenza A virus (IAV) infection. Progesterone treatment altered the inflammatory environment of the lungs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(135 citation statements)
references
References 60 publications
5
128
0
2
Order By: Relevance
“…Taken together, these studies indicate that activation of EGFR contributes to fibrosis and that inhibition of EGFR signaling can protect against fibrosis. Studies on influenza A virus show that amphiregulin protects against virus-induced lung pathology in female mice, further complicating the picture (59). Other studies have also shown that tyrosine kinase inhibitors exacerbate PF (60) and that conditional loss of the EGFR ligand HB-EGF contributes to liver fibrosis (61), demonstrating the complex nature of EGFR signaling pathway integration.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these studies indicate that activation of EGFR contributes to fibrosis and that inhibition of EGFR signaling can protect against fibrosis. Studies on influenza A virus show that amphiregulin protects against virus-induced lung pathology in female mice, further complicating the picture (59). Other studies have also shown that tyrosine kinase inhibitors exacerbate PF (60) and that conditional loss of the EGFR ligand HB-EGF contributes to liver fibrosis (61), demonstrating the complex nature of EGFR signaling pathway integration.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte macrophage colony-stimulating factor (GM-CSF)-induced AREG production reduces susceptibility of post-influenza staphylococcal pneumonia co-infection [104]. Additionally, progesterone (P4) can protect female mice against influenza infection by upregulating AREG production in respiratory epithelial cells to improve wound healing [105]. Based on the current studies on AREG in the context of influenza infection, AREG contributes to lung recovery and restores lung function, and may have great potential as a therapeutic.…”
Section: Cytokines Induced By Immune Responses (Secondary Cytokines)mentioning
confidence: 99%
“…Tissue sections (8 um) were cut, mounted on glass slides, and stained as described previously (Hall et al, 2016). Tissue sections (8 um) were cut, mounted on glass slides, and stained as described previously (Hall et al, 2016).…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%